Redistribuição e reconhecimento na liberdade assistida em São Paulo: entre afirmação e desconstrução da identidade de gênero das adolescentes - Vieira, Lais Silva [UNIFESP] (2020)
The object of this research is the social-educative care offered to young females in juvenile probation in the city of São Paulo. The field research was conducted in five services that offer the non-custodial measure of juvenile probation in the city of São Paulo. The central question is to analyze the potential of probation in promoting the affirmation or transformation of the gender identities of these adolescents, considering the material (redistributive) and symbolic (recognition) dimensions of their trajectories. This task of considering these aspects is urgent because socio-educational policies focus on the economic dimension as the center of socio-educational interventions and, in doing so, neglect the symbolic dimension while ignoring other markers that affect this population as gender and class.